The Effect of Magnetic Fields on Wound Healing: Experimental Study and Review of the Literature - Henry, Steven L (Open Science Company, LLC, 2008)
Objective: Magnets are purported to aid wound healing despite a paucity of scientific evidence. The purpose of this study was to evaluate the effect of static magnetic fields on cutaneous wound healing in an animal model. The literature was reviewed to explore the historical and scientific basis of magnet therapy and to define its current role in the evidence-based practice of plastic surgery. Methods: Standardized wounds were created on the backs of 33 Sprague-Dawley rats, which were divided into 3 groups with either a 23 gauss magnet (group 1), a sham magnet (group 2), or nothing (group 3) positioned over the wound. The rate of wound closure by secondary intention was compared between the groups. Literature review was conducted through searches of PubMed and Ovid databases for articles pertinent to magnets and wound healing. Results: Wounds in the magnet group healed in an average of 15.3 days, significantly faster than those in either the sham group (20.9 days, P = .006) or control group (20.3 days, P < .0001). There was no statistically significant difference between the sham and control groups (P = .45). Conclusions: An externally applied, low-power, static magnetic field increases the rate of secondary healing. Review of the literature reveals conflicting evidence regarding the use of magnetic energy to aid the healing of bone, tendon, and skin. Level I studies are lacking and difficult to execute but are needed to define conclusively the role of magnets in clinical practice.